Recent Trends in Advanced Contact Lenses. Issue 10 (2nd April 2019) - Mutlu, Zeynep; Shams Es‐haghi, Siamak; Cakmak, Mukerrem
Abstract: Exploiting contact lenses for ocular drug delivery is an emerging field in the area of biomedical engineering and advanced healthcare materials. Despite all the research conducted in this area, still, new technologies are in their early stages of the development, and more work must be done in terms of clinical trials to commercialize these technologies. A great challenge in using contact lenses for drug delivery is to achieve a prolonged drug release profile within the therapeutic range for various eye‐related problems and diseases. In general, desired release kinetics to avoid the initial burst release is the zero‐order kinetics within the therapeutic range. This review highlights the new technologies developed to achieve efficient and extended drug delivery. It also provides an overview of the materials and methods for fabrication of contact lenses and their mechanical and optical properties. Abstract : This review focuses on the recent developments in ocular drug delivery via contact lenses (CLs). It summarizes the recent technologies developed to achieve an extended and efficient drug release. It also provides an overview of the materials and methods for fabrication of contact lenses and their mechanical and optical properties.